An analytical model for heat transfer characteristics of a deep-buried U-bend pipe and its heat transfer performance under different deflecting angles. (1st April 2022) - Li, Chao; Jiang, Chao; Guan, Yanling
Abstract: This study develops an analytical model for calculating heat transfer characteristics of deep-buried U-bend pipes. The model considers actual thermophysical parameters and a non-uniform ground temperature distribution around the buried pipes. To discuss the analytical model's applicability in both short- and long-term heat transfer operations, the study combines a 72-h field experiment and a 2904-h numerical simulation, verifying the analytical model. The field experiment was conducted on a project comprising deep-buried U-bend pipes at a 2781 m depth in Xi'an and served as a basis for establishing the numerical model. The experimental values and analytical solutions of buried pipes' heat transfer intensity within 72 h are compared, revealing a 10.47 kW time-weighted average of the absolute differences in 8–72 h period. The buried pipes' heat transfer intensity of both the analytical and the numerical solutions was tracked over 2904 h, yielding a 10.58 kW time-weighted average of absolute differences between the analytical and the numerical solutions over a period of 8–2904 h. The established analytical model enables the discussion of the heat transfer performance of U-bend buried pipes at different deflecting angles and promotes providing the design suggestions for deflecting angles in practical engineering. Highlights: U-bend DGHE field experiment at a depth of 2781 m was designed. An analytical model for heat transfer of U-bend DGHE was established. Short-term and long-term calculations of the analytical model were verified. Heat transfer performance of U-bend DGHE under different α was studied.